A tale of two cultures: The Omani–Indian encounter in the literature classroom. (October 2013) - Heble, Ayesha; Mehta, Sandhya Rao
The inclusion of cultural and contextual approaches in the study of literature has long been accepted as imperative in the literature classroom, fostering, as it does, the sensitization of students to diverse worldviews. This article aims to explore the way in which literature could affect students' preconceived notions of communities and people by using a specific context within the Middle East, that of the Indian community in Oman. The historical relationship between Oman and India is a complex one, including as it does a little-known historical narrative and a contemporary reality which includes stereotypes of the Indian community. Using the example of a classroom experience, this study looks into the ways in which literary texts, when dealt with in a contextual manner, afford a critical understanding of communities and succeed in correcting misconceptions by allowing for a dynamic relationship between two groups of people whose encounters with each other become layered and complex.